Effects of Hyul-Bu-Chuke-Tang on Erythrocyte Deformability and Cerebrovascular CO2 Reactivity in Normal Subjects. (28th May 2012) - Jung, Woo-Sang; Park, Joo-Young; Byeon, Hyung-Sik; Kim, Young-Jee; Park, Jung-Mi; Park, Seong-Uk; Cho, Seung-Yeon; Moon, Sang-Kwan
Abstract : Aim . Hyul-bu-chuke-tang (HCEt) is a well-known traditional herbal medicine that is used for the treatment of ischemic cerebrovascular disorders. We investigated the acute effects of HCEt on erythrocyte deformability and cerebrovascular CO2 reactivity (CVR) in healthy male subjects. Materials and Methods . We examined erythrocyte deformability in an HCEt group (n = 14 ) and a control group (n = 10 ). CVR was measured using hyperventilation-induced CO2 reactivity of the middle cerebral artery and transcranial Doppler (TCD) in the HCEt group (n = 11 ). A historical control group (n = 10 ) of CVR measurements was also created from our previous study. All measurements were performed prior to and 1, 2, and 3 hours after HCEt administration. Results . HCEt significantly improved erythrocyte deformability 1 hour after administration compared to the control group (2.9 ± 1.1 % versus - 0.6 ± 1.0 %, P = 0.034 ). HCEt significantly improved the CVR 2 hours after administration compared to the historical control group (9.1 ± 4.0 % versus - 8.1 ± 4.1 %, P = 0.007 ). The mean blood pressure and pulse rate did not vary from baseline values in either group. Conclusions . We demonstrated that HCEt improved erythrocyte deformability and CVR. Our findings suggest that an improvement in erythrocyte deformability contributes to HCEt's effect on cerebral microcirculation.